LEXICAL-SEMANTIC FEATURES OF ENGLISH AND UZBEK TOPONYMS - Mirboyeva Kibriyo (International Journal on Integrated Education, 2023)
In the language of each nation there are stable figurative turns that are reproduced in speech like a word, and are not created in the process of communication or writing a text. Such stable combinations are called phraseological units, phraseological units or phraseological turns. Lexical-semantic features of such units and words are analyzed.